Analysis of the Effect of Perceived Risk, Perceived Usefulness and Attitude on Usage Intention with TAM (Case Study: Go-Jek Application) - Yosi Afandi; Endang Astuti; Andriani Kusumawati; Yusri Abdillah (Politeknik Negeri Madiun, 2020)
The purpose of this research is to determine what variables affect usage intention. This research uses the object of research is the Go-Jek application. The Go-Jek application is one of the online transactions used by the community because the Go-Jek application provides various service features that are needed by the public such as Go-Ride, Go-Car, Go-Food, Go-Send and many more service features. With more and more users it is necessary to do research on Go-Jek applications. The method used in this research is TAM. The results of the test indicate that usage intention is influenced by variables of trust, perceived risk, perceived usefulness and attitude.